Early Growth of Acacia mangium × Acacia auriculiformis Hybrid in a Clonal Test at Three Different Sites in Indonesia - Sri Sunarti; Budiyansah Budiyansah; Arif Nirsatmanto (Jurnal Manajemen Hutan Tropika, 2018)
Abstract